2018
DOI: 10.1007/s10549-018-4960-2
|View full text |Cite
|
Sign up to set email alerts
|

CCN6 regulates IGF2BP2 and HMGA2 signaling in metaplastic carcinomas of the breast

Abstract: These data shed light into the pathogenesis of metaplastic carcinoma and demonstrate a novel CCN6/IGF2BP2/HMGA2 oncogenic pathway with biomarker and therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 36 publications
(64 reference statements)
2
28
0
Order By: Relevance
“…We found a high expression of IGF2BP2 in HNSCC tumor tissues and verified this result in our laboratory using immunohistochemistry. This is consistent with previous studies of IGF2BP2 in cancers, including colorectal cancer (Wang et al, 2019), gastrointestinal cancer (Zhou et al, 2017), endometrial cancer (Hiramatsu et al, 2016), pancreas cancer (Xu et al, 2019), breast cancer (McMullen et al, 2018), and hepatic carcinoma. We found that the upregulation of IGF2BP2 had some statistical correlation with the T stage, HPV status, and overall survival in HNSCC.…”
Section: Discussionsupporting
confidence: 93%
“…We found a high expression of IGF2BP2 in HNSCC tumor tissues and verified this result in our laboratory using immunohistochemistry. This is consistent with previous studies of IGF2BP2 in cancers, including colorectal cancer (Wang et al, 2019), gastrointestinal cancer (Zhou et al, 2017), endometrial cancer (Hiramatsu et al, 2016), pancreas cancer (Xu et al, 2019), breast cancer (McMullen et al, 2018), and hepatic carcinoma. We found that the upregulation of IGF2BP2 had some statistical correlation with the T stage, HPV status, and overall survival in HNSCC.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, Ccn6, secreted by normal breast epithelium, can suppress the expression of IGF2BP2 protein in cancerous breast tissues, thus modulating the growth of the tumor. Ccn6/Wisp3 knockdown up-regulated the expression of IGF2BP2 in mice, who developed mammary carcinomas characterized by spindle and squamous differentiation, validated hallmarks of metaplastic breast carcinomas [ 74 ] (Fig. 3 ).…”
Section: Igf2bp2 and Cancersmentioning
confidence: 99%
“…Collectively, these studies suggest that CCN6, IGF2BP2, and HMGA2 signaling pathway may play a functional role in the development of spindle and squamous metaplastic carcinomas, with promise as biomarkers and potential targets. 44…”
Section: New Promising Molecular Alterations In Metaplastic Carcinommentioning
confidence: 99%